(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents an analysis of the development of the professional skills of a modern rehabilitator, necessary for the formation of his professional worldview and intercultural competence. Competences of a rehabilitator are analyzed as tasks related to activities that he can successfully solve in the course of kinesotherapy. The profession of a rehabilitator involves communicative interaction with people who have various health disorders. Cognitive disorders and various disorders of the psycho-emotional state are more often observed in clients. Rehabilitation specialists note that in the process of receiving education they learn various methods of communicative interaction with clients, but at work they often have to work with clients who are representatives of different cultures, which sometimes leads to communicative misunderstandings. Thus, the problem of interaction between the rehabilitator and the client at the cross-cultural level arises, which must be solved directly in the process of kinesotherapy. A competent rehabilitation specialist must understand that his personal traits are an indicator of his professional activity in the process of intercultural communication with the client and his family members, as well as the level of his culture and competence. Intercultural competence demonstrates the personality traits of a rehabilitation specialist, it is formed and manifested not only in the process of communicative interaction with the client. This fact has a direct impact on the organization of the kinesotherapy process at all levels of interaction. A rehabilitologist, taking into account his professional activity, must be a model of tolerance in the most diverse situations and interact with clients on the basis of understanding and accepting their distinguishing features, which at the same time will reflect the personality trait of the rehabilitator. The goal of such communicative interaction is the formation of a competent specialist, capable of making decisions taking into account the individual characteristics of a person, who is able to understand his cultural diversity.